Docetaxel and anthracycline in neoadjuvant treatment of breast cancer. Efficacy evaluation according to molecular factors - Szydłowska-Pazera, Katarzyna; Potemski, Piotr; Kubiak, Robert; Płużańska, Anna (Contemporary Oncology/Współczesna Onkologia, 2007)
Background: Molecular markers of proliferation (Ki-67 antigen) and apoptosis (P53 and Bcl-2 protein) are among the most extensively examined prognostic and predictive factors of neoadjuvant chemotherapy with taxoid and anthracycline. Aim: The assessment of molecular factors associated with clinical response and prognosis. Patients and methods: The study was conducted on a group of 50 women aged 37-81 with locally advanced, primary inoperable breast cancer. All patients were treated in the Regional Oncology Center in £ódź between April 2001 and December 2004. They received two-drug combination of docetaxel at a dose of 75 mg/m2 and anthracycline (doxorubicin 50 mg/m2 or mitoxantrone 12 mg/m2). The clinical response was assessed according to RECIST criteria. For all patients, primary paraffin-embedded tumor specimens were available. Immunostaining for Ki-67 antigen, P53 protein, and Bcl-2 protein was done in the Pathology Department, Chair of Oncology, Medical University of £ódź. Results: Objective response was observed in 84% of patients; CR (complete response) in 4%, PR (partial response) in 80%. SD (stable disease) classified as no response was seen in 16% of patients. No PD (disease progression) was observed. High expression of Ki-67 antigen after chemotherapy was associated with the worse efficacy of the treatment. The relative risk of recurrence was lower by 73% when Bcl-2 protein was found in tumor cells. High expression of Ki-67 and P53 positivity were associated with an increase of the relative risk of recurrence over three-fold. Patients with tumors positive for P53 protein were at three-fold higher risk of cancer-related death. Conclusions: In patients with locally advanced breast cancer, combination of docetaxel and anthracycline almost always leads to the achievement of tumor remission and allows definitive surgery. Ki-67 expression is associated with clinical response. Ki-67, P53 and Bcl-2 expression are prognostic factors.